Beyond Bigger Models: Multi-Axis Scaling for Large Language Models - Reeshav Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2026)
For years, the dominant prescription for building capable large language models (LLMs) was deceptively simple: make the model bigger. That logic produced real results with GPT-3’s 175 billion parameters, delivering in-context learning across dozens of benchmarks. However, the assumption that parameter count is the primary lever for system quality is no longer tenable with Chinchilla demonstrating that most landmark models were significantly undertrained relative to their size. What followed was not a replacement of the scaling paradigm but a proliferation of it. Modern LLM systems are now shaped by nine distinct scaling axes: pretraining scale, compute-optimality, sparse conditional computation, retrieval and memory augmentation, long-context modeling, post-training alignment, parameter-efficient adaptation (PEFT), reasoning-time compute, and serving infrastructure optimization. This paper evaluates each axis against four operational dimensions (capability, cost, latency, and governance burden) and presents a product decision framework to minimize enterprise failure modes by selecting the most efficient scaling interventions. The central finding is that the AI systems that consistently outperform in production are those built on a coherent portfolio of axis choices, not those with the largest base model.